Tourist Voucher Effectiveness and Perception Among Entrepreneurs in The Tourism Sector in Poland - Joanna STEFANCZYK (Communications of International Proceedings, 2025)
The poor situation on the Polish-Belarus border may be contributing to a decline in demand for tourism services in the border region. The regional government has initiated an intervention tool in the form of a tourist voucher valid in selected region. The newly created Podlasie Tourist Voucher functions in 2025 and is financed from the budget of the local government unit. It aims to increase tourist interest in staying in accommodation facilities in Podlasie in 2025. The article provides an overview of reports on the new intervention tool and a review of the literature on tourism support in Poland.
Keywords: Tourism; Intervention tools; Poland; Hotel industry.